2012
DOI: 10.1103/physreva.85.021803
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon interferences with degenerate and nondegenerate paired photons

Abstract: We generate narrow-band frequency-tunable entangled photon pairs from spontaneous four-wave mixing in three-level cold atoms and study their two-photon quantum interference after a beam splitter. We find that the path-exchange symmetry plays a more important role in the Hong-Ou-Mandel interference than the temporal or frequency indistinguishability, and observe coalescence interference for both degenerate and nondegenerate photons. We also observe a quantum beat in the same experimental setup using either slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…In the same year, Ou et al reported a similar beating experiment with blue and green laser light beams [9]. The second-order interference with photons of different spectra was further studied with photons generated by spontaneous parametric down conversion [10][11][12][13][14][15][16], single-photon sources [17], laser and single-photon source [18], chirped laser pulses [19], and spontaneous Raman process [20], etc. These experiments can be categorized into two groups.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the same year, Ou et al reported a similar beating experiment with blue and green laser light beams [9]. The second-order interference with photons of different spectra was further studied with photons generated by spontaneous parametric down conversion [10][11][12][13][14][15][16], single-photon sources [17], laser and single-photon source [18], chirped laser pulses [19], and spontaneous Raman process [20], etc. These experiments can be categorized into two groups.…”
Section: Introductionmentioning
confidence: 94%
“…These experiments can be categorized into two groups. One group is that the two light beams of different spectra are incident to both input ports of a Hong-Ou-Mandel (HOM) interferometer [8][9][10][11][12][13][14][15][16]20]. The other group is that two light beams are incident to the two input ports of a HOM interferometer, respectively [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. We work with right-angle SFWM in laser-cooled 85 Rb atoms loaded in a magneto-optical trap [33]. The energy difference of the two hyperfine ground states j1i ¼ j5S 1=2 ; F ¼ 2i and j2i ¼ j5S 1=2 ; F ¼ 3i is ℏΔ 21 , with Δ 21 ¼ 2π × 3036 MHz.…”
mentioning
confidence: 99%
“…1(a). We produce narrowband photon pairs from SFWM in lasercooled 85Rb atoms in a three-dimensional magneto-optical trap driven by two coherent (pump and coupling) laser fields [24]. The atomic cloud has a diameter of about 1.3 mm.…”
Section: Polarization-frequency-coupled Entanglement: Theory and mentioning
confidence: 99%